Performance and Safety of the Extended Depth of Focus Implantable Collamer ® Lens (EDOF ICL) in Phakic Subjects with Presbyopia - Packer, Mark; Alfonso, Jose F; Aramberri, Jaime; Elies, Daniel; Fernandez, Joaquin; Mertens, Erik (Clinical ophthalmology (Auckland, N.Z.), 2020)
To evaluate the performance and safety of the Extended Depth of Focus Implantable Collamer Lens (EDOF ICL) for improvement of uncorrected near, intermediate and distance visual acuity in phakic subjects with myopia and presbyopia. Prospective multicenter study. Presbyopic subjects who required an EDOF ICL in the range of -0.50 D to -18.00 D, exhibited ≤ 0.75 D refractive astigmatism and required from +1.00 to +2.50 D reading add were implanted bilaterally. Assessments at 6 months included uncorrected near, intermediate and distance visual acuities, defocus curves, contrast sensitivity, responses to the National Eye Institute Refractive Error Quality of Life Questionnaire and a Task Assessment Questionnaire. A total of 34 subjects completed the study. Investigators targeted emmetropia in all eyes. Mean binocular uncorrected near, intermediate and distance visual acuities measured logMAR -0.01 ± 0.05 (20/20), -0.02 ± 0.08 (20/19) and 0.07 ± 0.10 (20/23), respectively. Mean monocular uncorrected near, intermediate and distance visual acuities measured logMAR 0.068 ± 0.09 (20/23), 0.062 ± 0.10 (20/23) and 0.16 ± 0.12 (20/29). There were no clinically or statistically significant differences in contrast sensitivity between baseline and 6 months under any testing conditions. Subjects reported significant improvements in measures of vision-related quality of life and ability to perform tasks at all distances without glasses or contact lenses. Overall, satisfaction with the EDOF ICL was high: postoperatively, 91.2% of subjects were satisfied with their vision. This multicenter, prospective clinical investigation demonstrated the ability of the EDOF ICL to correct myopia and presbyopia, resulting in improvement of uncorrected near, intermediate and distance visual acuity without compromising the quality of vision. The EDOF ICL allowed subjects to perform tasks of daily living without glasses or contact lenses. Subjects reported significant improvements in quality of life with high levels of spectacle independence and satisfaction.